Rumex crispus and Cordyceps militaris Mixture Ameliorates Production of Pro-Inflammatory Cytokines Induced by Lipopolysaccharide in C57BL/6 Mice Splenocytes - Park, Eui-Seong; Song, Gyl-Hoon; Kim, Seung-Hee; Lee, Seung-Min; Kim, Yong-Gyu; Lim, Yaung-lee; Kang, Soon Ah; Park, Kun-Young (Preventive nutrition and food science, 2018)
(Rc) and (Cm) mixture (Rc-Cm; AST2017-01) ameliorated production of proinflammatory cytokines, inflammation-related genes, and nitric oxide (NO) induced by lipopolysaccharide (LPS) in mouse splenocytes. Rc-Cm (6:4) and Taemyeongcheong (commercial healthy drink containing Rc-Cm) were co-administered along with LPS. Rc-Cm inhibited production of tumor necrosis factor α, interferon γ, interleukin (IL)-1β, and IL-6 in LPS-induced splenocytes. However, levels of inflammatory cytokines were elevated in the absence of LPS treatment. Rc-Cm significantly suppressed mRNA expression of IL-1β, IL-6, and the inflammation-related genes inducible NO synthase (iNOS) and cyclooxygenase 2 (COX-2), as well as NO production upon LPS co-treatment. Whereas Rc-Cm increased mRNA expression of IL-1β, and IL-6, but did not up-regulate expression of iNOS and COX-2, or increase NO production without LPS co-treatment. Therefore, treatment of Rc-Cm to LPS-induced splenocytes ameliorated induction of pro-inflammatory cytokines, inflammation-related genes, and NO production. In the absence of LPS, Rc-Cm treatment up-regulated pro-inflammatory cytokines but did not alter expression of the inflammation-related genes iNOS and COX-2 or NO production. These results indicate that the natural phytochemicals chrysophanol and cordycepin in Rc-Cm promote anti-inflammatory activities and immune cell responses.